SONGKET BUNGO TANJUNG DI KABUPATEN BUNGO PROVINSI JAMBI (Studi Kasus Pada Industri Songket Bungo Tanjung) - Novitasari, Puput; Ernawati, Ernawati; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2015)
Â  This study aimed to describe about the craft of SongketBungoTanjung which includes decorative and the meanings which contained in Songket motifs Tenunan Sogket Bungo Tanjung. The method used is descriptive qualitative method. Collecting data in this study was using techniques of observation, interviews and documentation. The results showed that the SongketBungoTanjung consists of six motifs derived from naturalist decoration which have functional characteristic namely: KapalSenggat, Duren Pecah, Kembang Duren, Teratai di Atas Air, Teratai di Dalam Air and Merak. While, the decorative pattern which used to fill the field of ornamental patterns and decorative patterns symmetrical periphery. As the meaning of the motif is Kembang Duren means a child that must be given knowledge from childhood, Teratai means flower that grows in Bungo and into the first history which came to Bungo, Duren Pecah means the people who is knowledgeable will always be good at keeping themselves, Motif KapalSenggat means in life we have to be introspective and cautious, Merak implies the meaning of the sacrifice of a mother is very large. key word: Songket, Bungo Tanjung